ANALISIS KINERJA RUAS JALAN AKIBAT BANGKITAN PERGERAKAN DI PASAR PANDAK GEDE - Karnata Mataram, Nyoman (Jurnal Ilmiah Teknik Sipil, 2012)
The rapid development in a region is normally followed by the increase in movement occurred in that region. In Kediri district of Tabanan, the market activity has increased trip generation that leads on the traffic conflict. The presence of Pandak Gede Market has caused traffic problems including road performance impairment caused by on street parking, loading and unloading of goods, the street vendors and pedestrian activity entering and exiting the market. The data used in this study are primary and secondary data. The primary data included traffic volume, market trip generation, road inventory, speed, and side friction. The secondary data are obtained from Tabanan Central Statistics Agency (BPS) consisting, Tabanan city population and the number of vehicle ownership. Road performance analysis is based on the Indonesian Highway Capacity Manual (IHCM) in 1997. In addition the growth factor model is used to predict the road performance for the next 10 years.
Keywords: trip generation, road performance.